Tratamento Flexível e Eficiente da Migração de Objetos Java em Aplicações Bulk Synchronous Parallel - Graebin, Lucas (Universidade do Vale do Rio dos Sinos, 2012)
Process migration is an useful mechanism for runtime load balancing, mainly in heterogeneous and dynamic environments. In particular, this technique is important for Bulk Synchronous Parallel (BSP) applications. This kind of application is based in rounds, or supersteps, where the time of each superstep is determined by the slowest process. In this context, this work presents the jMigBSP system. It was designed to act over BSP-based Java applications and its differential approach concerns the offering of the rescheduling facility in two ways: (i) by using migration directives in the application code directly and; (ii) through automatic load balancing at middleware level. In addition, the presented library makes the object interaction easier by providing one-sided asynchronous communication. The development of jMigBSP was guided by the following ideas: efficiency and flexibility. First of all, the efficiency topic involves the performance relation with compiled languages (native code), as well as the time spent in the rescheduling algorithm itself. Moreover, the flexibility is present in the treatment of automatic object rescheduling. The evaluation of jMigBSP comprised the development and execution of two BSP applications in a multicluster environment: (i) fast Fourier transform and; (ii) Fractal image compression. Two heuristics were used for selecting the candidate objects for migration in the evaluation. The first heuristic chooses the BSP object that presents the highest PM (Potential of Migration) value. The second heuristic selects a percentage of objects based on the highest PM value. The results showed that jMigBSP offers an opportunity to get performance in an effortless manner to the programmer since its does not need modifications in the application code. jMigBSP makes possible gains of performance up to 29% as well as produces a low overhead when compared with a C-based library. Furthermore, an average overhead of 5,52% was observed in the rescheduling algorithm. In general, the results demonstrate in practice the theory of process migration, where computationally intensive applications (CPU-bound) are most benefited by the entities transferring (processes, tasks or objects) to faster processors. Considering that the selection of a percentage of objects for migration showed an efficient heuristic, future work includes the development of new mechanisms that select a collection of objects without the need to setup particular parameters to the rescheduler.
Keywords: Bulk synchronous parallel; Java; Reescalonamento; Balanceamento de carga; Rescheduling; Load balancing; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação